Implikasi Perawatan Partial Edentulous dengan Alveolar Ridge Klasifikasi Klas III Nallaswamy - Tara Yurian Nadhifa; Retno Sari (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Background: Nallaswamy Class III alveolar ridge refers to an edentulous alveolar bone that has undergone resorption, resulting in a moderate ridge height with a knife-edge ridge form. This condition is relatively common and has been reported to reach a prevalence of approximately 89% in edentulous mandibles. Objective: To describe the prosthodontic treatment implications in patients with Nallaswamy Class III alveolar ridge using an acrylic resin removable partial denture (RPD). Case Report: A 22-year-old female patient presented to RSGM Soelastri with complaints of discomfort while chewing due to the loss of several posterior teeth in the mandible. The teeth had been extracted three years earlier due to caries and retained roots. Intraoral examination revealed healthy dentition in the maxillary arch and edentulous areas at teeth 35, 36, 45, and 46 in the mandibular arch. The alveolar ridge in the edentulous area showed a knife-edge form with moderate height, consistent with Nallaswamy Class III. Discussion: The condition was classified as Applegate-Kennedy Class III modification 1P with bilateral bounded saddle areas, which may affect mastication, aesthetics, and speech. Conclusion: Partial edentulism with a knife-edge alveolar ridge can be effectively managed using an acrylic resin removable partial denture.